Analisis Strategi Pengelolaan Dana Zakat, Infaq, Shadaqah (ZIS) Dalam Mendorong Optimalisasi Pencapaian BAZNAS Microfinance Masjid (Studi Lembaga BAZNAS Kota Cilegon) - Farhan Zulfahmi; Evi Ekawati; Ahmad Hazas Syarif (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the management strategies of zakat, infaq, and sadaqah (ZIS) implemented by BAZNAS Cilegon City in optimizing the Baznas Microfinance Masjid (BMM) program as an instrument for empowering the ummah’s economy. The research employs a qualitative approach with data collected through interviews, observations, and documentation, and validated using methodological triangulation. Data analysis follows Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The findings reveal that BAZNAS Cilegon City applies digital-based fundraising strategies, transparency- and accountability-oriented management, and productive zakat distribution through mosque-based microfinance. The SWOT analysis identifies institutional legitimacy and mosque social networks as strengths, industrial zakat potential as an opportunity, and limitations in human resources and digital reporting systems as weaknesses. Empirically, the BMM program enhances mustahik income, independence, and social participation, aligning with the principles of maqashid al-shariah. This study confirms that mosque-based productive ZIS management plays a significant role in shifting the paradigm from consumptive zakat toward sustainable empowerment-oriented zakat.